2022
DOI: 10.4103/jfmpc.jfmpc_1162_21
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of multiplex-PCR for the diagnosis of acute bacterial meningitis

Abstract: Background and Objectives: Prompt and accurate diagnosis of acute bacterial meningitis (ABM) is critical for patient management. We designed and evaluated two sets of multiplex-PCR assays for the simultaneous detection of six major etiologies of ABM i.e., Streptococcus pneumoniae, Haemophilus influenzae type b, and Neisseria meningitidis in one set and Listeria monocytogenes, Streptococcus agalactiae, and Escherichia coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Molecular detection assays increase diagnostic accuracy for bacterial infections in individuals who are receiving or have received broad spectrum antimicrobials that may decrease sensitivity of bacterial cultures [25] , [26] , [27] , [28] . Bacterial maningitis with normal CSF analysis has been previously reported [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Molecular detection assays increase diagnostic accuracy for bacterial infections in individuals who are receiving or have received broad spectrum antimicrobials that may decrease sensitivity of bacterial cultures [25] , [26] , [27] , [28] . Bacterial maningitis with normal CSF analysis has been previously reported [29] .…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently challenging to distinguish between bacterial and nonbacterial aetiologies due to comparable clinical presentation. Procalcitonin level is a potentially sensitive measure of severe bacterial infections, including meningitis, numerous studies have shown that bacterial illnesses, such as meningitis, are associated with elevated serum PCT values (3,6) .…”
Section: Discussionmentioning
confidence: 99%
“…The definitive diagnosis is the presence of meningococci in the blood, CSF, throat swab, or skin biopsy from the rash. Furthermore, CSF analysis typically reveals high protein, low glucose, CSF with a glucose to blood glucose ratio of 0.4 or lower, high lactate, and high neutrophils [ 58 , 59 , 60 , 61 ]. Antimicrobials most commonly used to eradicate meningococci include penicillin, rifampin, ciprofloxacin, and ceftriaxone [ 62 , 63 , 64 ].…”
Section: Group 1: Dms Denoting Life-threatening Skin Diseases That Re...mentioning
confidence: 99%